2017
DOI: 10.1037/int0000090
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition as a predictor of change in the treatment for borderline personality disorder: A preliminary pilot study.

Abstract: There is evidence that a key feature in borderline personality disorder (BPD) is the difficulty to reflect on one's own as well as on other people's state of mind. So far, no study has examined the link between metacognition and symptom change presented by BPD patients across treatment. This preliminary pilot study represents a first step in describing impairments in different dimensions of metacognition and their connection with the symptoms presented by a N ϭ 10 BPD sample. The transcripts from the first and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
2
24
1
1
Order By: Relevance
“…Cronbach's alpha was α = .94 for the present study and .91 for the pilot study (Maillard et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cronbach's alpha was α = .94 for the present study and .91 for the pilot study (Maillard et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…In a pilot study, pre–post therapy session transcripts of 10 BPD patients were analysed with the MAS‐R (Maillard et al ., ). The findings, to be taken cautiously, showed significant improvement in the metacognition's mastery function and a link between the level of understanding of others’ mind at the treatment onset and better outcomes after a short‐term treatment.…”
Section: Introductionmentioning
confidence: 97%
“…This is proposed to lead to therapeutic change when it promotes an awareness of maladaptive schemas, allows access to healthy aspects of the self and increases the ability to plan behaviours consistent with one's wishes in everyday life. Evidence supporting MIT includes several case series that indicated a reliable clinical change in symptoms and interpersonal functioning, 41,42 including a pilot RCT reporting encouraging results for a group intervention on PD. 43 Findings for the group-based approach to MIT have been reported in an open trial 44 and in a pilot study including clients with borderline personality disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Levy and colleagues (2006) examined change in three forms of psychotherapy for BPD --TFP, DBT and supportive therapy -and found that only TFP was associated with an increase in mentalizing functions, along with development of more secure attachment patterns in some patients in this group [29]. Consistent results were presented by Fischer-Kern and colleagues [61] (see also de Meulemeester et al [62]; Maillard et al, [63]). Other research has underlined the moderating factor of mentalizing capacities for outcome for different categories of PD [64,65].…”
Section: Mechanisms Of Change In Treatments For Borderline Personalitmentioning
confidence: 70%